Embryonic sympathoblasts transiently express TrkB in vivo and proliferate in response to brain-derived neurotrophic factor in vitro - Straub, Jennifer A (BioMed Central, 2007)
BACKGROUND: Nerve growth factor and neurotrophin-3 are involved in the development of sympathetic neurons; however, whether brain derived neurotrophic factor also plays a role is not known. The purpose of this study was to determine whether BDNF and its receptor, TrkB, are expressed during the development of paravertebral sympathetic ganglia in vivo and to determine the effect of BDNF in vitro. RESULTS: As neural crest cells coalesce to form sympathetic ganglia, TrkB-positive cells are seen in both chicken and mouse embryos. In chicken embryos, TrkB-expressing cells first appear at Hamburger-Hamilton Stage (St) 27 and they co-express HNK-1, confirming that they are migrating neural crest cells. The TrkB-positive cells lack neural markers at this stage; however, they migrate with other neurally differentiating cells that are TrkA and TrkC-positive. By St. 29/30, TrkB-positive cells begin to express the neural specific markers Hu C/D and Islet-1; eventually, all TrkB positive cells commence neural differentiation. By St. 34, TrkB and TrkC staining are lost. BDNF transcript expression parallels that of TrkB. In the mouse, TrkB-positive cells surround newly formed sympathetic ganglia and a small number of TrkB positive cells that co-express tyrosine hydroxylase are seen within ganglia between E13.5-15. In cell culture, many cells from St. 29–30 chicken lumbar sympathetic ganglia express neural markers and are dividing, indicating that they are sympathoblasts. Sympathoblasts and neurons require both nerve growth factor and neurotrophin-3 for survival. BDNF increases the number of cells expressing neural markers in culture by increasing number of cells that incorporate bromodeoxyuridine. In contrast, most TrkB-positive sympathetic cells in vivo are not actively proliferating between E6–E8. CONCLUSION: Developing paravertebral sympathetic ganglia in avian and murine embryos contain a subpopulation of sympathoblasts that transiently express TrkB and ultimately commence neuronal differentiation. These TrkB expressing sympathoblasts are not actively dividing in vivo; yet, when placed in vitro, will divide in response to BDNF. This suggests that the availability of BDNF in vivo fails to reach a threshold necessary to induce proliferation. We suggest that excess TrkB stimulation of sympathoblasts in vivo may lead to the genesis of neuroblastoma.